Asuhan Kebidanan Komprehensif Pada Ny. D Dengan Kehamilan Dan Persalinan Normal Di Uptd Puskesmas Jamblang Kabupaten Cirebon - Fidya Ribillah; Yanti Susan (MEJORA Medical Journal Awatara, 2024)
Comprehensive care is an examination that is carried out thoroughly, in detail and continuously, starting from pregnant women, giving birth, postpartum and newborns, which is expected 10 reduce the maternal mortality rate which is the biggest problem in the world today. This journal aims to implement Normal Childbirth Care Management at the Jamblang Community Health Center in 2024 using a midwifery care approach with documentation using the SOAP method. The results of the case study conducted on Mrs. “D” with Normal Childbirth Care means that there are no obstacles found in dealing with problems with Normal Childbirth Care. In the management of normal delivery care for Mrs. “D”is carried out by providing clean and safe care and making efforts to prevent complications, especially post-natal bleeding, hypothermia and asphyxia of newborns, as well as monitoring and care from stages I to IV. The conclusion of the case study using a midwifery care approach with documentation using the SOAP method is that from stage I to IV everything went normally without any complications, no complications or problems were found in the fetus and mother, and the condition of the mother and baby was good as indicated by vital signs in normal limits.